2024
DOI: 10.3390/plants13030390
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Alleviates Salt Stress Effects on Gas Exchange, Growth, and Production of Naturally Colored Cotton

Jackson Silva Nóbrega,
Valéria Ribeiro Gomes,
Lauriane Almeida dos Anjos Soares
et al.

Abstract: Cotton is one of the most exploited crops in the world, being one of the most important for the Brazilian Northeast. In this region, the use of irrigation is often necessary to meet the water demand of the crop. Water is often used from underground wells that have a large amount of salt in their constitution, which can compromise the development of crops, so it is vital to adopt strategies that reduce salt stress effects on plants, such as the foliar application of hydrogen peroxide. Thus, the objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…The diversity of plants within the riparian area and variations in plant biomass can influence these changes. Alterations in soil moisture content can impact the structure of soil aggregates, subsequently leading to modifications in the physical and chemical properties of the soil [13]. Furthermore, studies have revealed that a decrease in soil moisture levels can result in a reduction in nutrients within the soil, subsequently influencing changes in plant cover [14].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of plants within the riparian area and variations in plant biomass can influence these changes. Alterations in soil moisture content can impact the structure of soil aggregates, subsequently leading to modifications in the physical and chemical properties of the soil [13]. Furthermore, studies have revealed that a decrease in soil moisture levels can result in a reduction in nutrients within the soil, subsequently influencing changes in plant cover [14].…”
Section: Introductionmentioning
confidence: 99%